A study on the Influence of Chinese University English teachers' emotions on their professional identity - Yao, Dingge; Mohammad Musab, Azmat Ali; Zuraina, Ali (Bilingual Publishing Group, 2025)
Emotions, as a form of expression of human inner feelings, play a vital role in teachers' professional development and affect the sense of professional identity. The current study, aims at identifying factors influencing teachers' emotional expression and management; exploring the effects of emotional triggers on teachers' professional identity; and analyzing the effects of Chinese University English teachers' emotions on their professional identity. Employing ten English teachers in one of the universities in China, a semi-structured interview was used in this study to investigate the factors influencing their emotions and professional identity. It also gauges how these factors impact teachers' professional identity. The findings generated three (3) themes of the factors that affect the expression and management of teachers' emotions. These are “sense of accomplishment and job satisfaction,” “happiness from student interactions and hopefulness”, and “frustration from high workload and lack of support.” The study found that personal traits and emotional intelligence, physical condition, working pressure, working environment and support, career development opportunities, social expectations, social recognition, and student feedback are the main factors affecting English teachers’ emotions and their professional identity. Besides, sense of accomplishment, satisfaction, happiness, frustration and anxiety are the emotional states that influence English teachers’ self-image of professional identity. This study links emotions to teachers' professional identity, highlighting key factors affecting English teachers' emotions. The findings have important implications for teacher training programs, educational policies, and classroom practices, providing insights into how to support teachers’ emotional well-being and strengthen their professional identity.